Assessment of the factors influencing consumer buying decision of mobile phone brands: A survey study among university students - Zephania, Glory (Mzumbe University, 2024)
A dissertation submitted to Mzumbe University as a partial fulfillment of the requirements for the award of the Degree of Master of Science in Marketing Management of Mzumbe University